Pelatihan Sport Education Model guna Meningkatkan Teacher’ Sense of Efficacy Guru Pendidikan Jasmani Sekolah Dasar di Kecamatan Lembang, Kabupaten Bandung Barat - Shela Ginanjar; Samsudin; Taufik Rihatno (PERDULI: Jurnal Pengabdian kepada Masyarakat, 2024)
Physical education teachers are often required to teach and coach in their schools. This has an impact on the Teacher's Sense of Efficacy aspect, so the Sport Education Model can be used as a solution. The aim of this research is to introduce the Sport Education Model and its relationship to the Teachers' Sense of Efficacy aspect. The research methodology is experimental with One Sample Pretest-Posttest Design. The population was 50 physical education teachers at elementary schools in Lembang District, West Bandung Regency and Total Sampling was used. The test instrument is the Teachers' Sense of Efficacy Questionnaire. Based on the Wilcoxon test results, Z is -7.005 with Sig. 0.000, this means that the Teacher' Sense of Efficacy variable for elementary school physical education teachers has increased significantly. Through the Sport Education Model training which has been implemented for elementary school physical education teachers in Lembang District, West Bandung Regency, they are able to improve basic skills and understanding of tactics and are able to increase Teacher's Sense of Efficacy.